Relational Thinking in Problem Solving Mathematics based on Adversity Quotient and Visual Learning Style - Inggar Dwi Pradika; Siti M Amin; Siti Khabibah (SAINTIS Publishing, 2019)
The purpose of this study is to describe the relational thinking profile of students of Quitter-Visual, Camper-Visual and Climber-Visual type in solving mathematical problems based on Polya rules. To support the research, we use qualitative descriptive method involving 30 students of grade V SDN Sawahan I Surabaya. The data were collected using math skill test and interview. The results show that, Climber-Visual type students are able to apply all polya steps properly and correctly and Camper-Visual type students are only able to understand the problem and implement it while the Quitter-Visual type students are less able to understand the problem and abandon it. The result is caused by students' endurance in facing difficulties. The findings of this study can be used to map effective and efficient learning methods.